Pro-inflammatory Diet Pictured in Children With Atopic Dermatitis or Food Allergy: Nutritional Data of the LiNA Cohort - Schütte, Olivia; Bachmann, Larissa; Shivappa, Nitin; Hebert, James R.; Felix, Janine F.; Röder, Stefan; Sack, Ulrich; Borte, Michael; Kiess, Wieland; Zenclussen, Ana C.; Stangl, Gabriele I.; Herberth, Gunda; et al. (Frontiers in Nutrition, 2022)
Lifestyle and environmental factors are known to contribute to allergic disease development, especially very early in life. However, the link between diet composition and allergic outcomes remains unclear. In the present population-based cohort study we evaluated the dietary intake of 10-year-old children and analyses were performed with particular focus on atopic dermatitis or food allergy, allergic diseases known to be affected by dietary allergens. Dietary intake was assessed via semi-quantitative food frequency questionnaires. Based on these data, individual nutrient intake as well as children’s Dietary Inflammatory Index (C-DII TM) scores were calculated. Information about atopic manifestations during the first 10 years of life and confounding factors were obtained from standardized questionnaires during pregnancy and annually thereafter. Analyses from confounder-adjusted logistic regression models (n=211) revealed that having atopic outcomes was associated with having a pro-inflammatory pattern at the age of 10 years: OR=2.22 (95% CI: 1.14–4.31) for children with atopic dermatitis and OR=3.82 (95% CI: 1.47-9.93) for children with food allergy in the first 10 years of life. A pro-inflammatory dietary pattern might worsen the atopic outcome and reduce the buffering capacity of the individual against harmful environmental exposures or triggers. For paediatricians it is recommended to test for the individual tolerance of allergenic foods and to increase the nutrient density of tolerable food items to avoid undesirable effects of eating a pro-inflammatory diet.